Cyclic GMP and PKG Signaling in Heart Failure - Numata, Genri; Takimoto, Eiki (Frontiers in Pharmacology, 2022)
Cyclic guanosine monophosphate (cGMP), produced by guanylate cyclase (GC), activates protein kinase G(PKG) and regulates cardiac remodeling. cGMP/PKG signal is activated by two intrinsic pathways: nitric oxide (NO)-soluble GC and natriuretic peptide (NP)-particulate GC (pGC) pathways. Activation of these pathways has been emerged as a potent therapeutic strategy to treat patients with heart failure, given cGMP-PKG signaling is impaired in heart failure with reduced ejection fraction (HFrEF) and preserved ejection fraction (HFpEF). Large scale clinical trials in patients with HFrEF have shown positive results with agents that activate cGMP-PKG pathways. In patients with HFpEF, however, benefits were observed only in a subgroup of patients. Further investigation for cGMP-PKG pathway is needed to develop better targeting strategies for HFpEF. This review outlines cGMP-PKG pathway and its modulation in heart failure.